Switching Hole and Electron Transports of Molecules on Metal Oxides by Energy Level Alignment Tuning - Bao, Zhong-Min; Xu, Rui-Peng; Li, Chi; Xie, Zhong-Zhi; Zhao, Xin-Dong; Zhang, Yi-Bo; Li, Yan-Qing; Tang, Jian-Xin (ACS applied materials & interfaces, 2016)
Charge transport at organic/inorganic hybrid contacts significantly affects the performance of organic optoelectronic devices because the unfavorable energy level offsets at these interfaces can hinder charge injection or extraction due to large barrier heights. Herein, we report a technologically relevant method to functionalize a traditional hole-transport layer of solution-processed nickel oxide (NiO x ) with various interlayers. The photoemission spectroscopy measurements reveal the continuous tuning of the NiO x substrate work function ranging from 2.5 to 6.6 eV, enabling the alignment transition of energy levels between the Schottky–Mott limit and Fermi level pinning at the organic/composite NiO x interface. As a result, switching hole and electron transport for the active organic material on the composite NiO x layer is achieved due to the controlled carrier injection/extraction barriers. The experimental findings indicate that tuning the work function of metal oxides with optimum energy level offsets can facilitate the charge transport at organic/electrode contacts.